PEMBELAJARAN TARI MERAK BAGI SISWA TUNAGRAHITA RINGAN DI SLB C CIPAGANTI BANDUNG - Intan Purnamasari (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2018)
Learning Merak Dance For Lightweight Students Of Disabilities At SLB C Cipaganti Bandung.This research is the background of the difficulty of dance learning for children with lightweight disabilities. Learning dance at SLB C Cipaganti Bandung has a high level of difficulty when compared with dance learning in ordinary schools, Because the students are lightweight children with disabilities,who have difficulty in motor and concentration, while in dancing is needed strong motion, concentration and memory On every movement on a dance. This study aims to determine the Learning Process, Media, Methods and evaluation used in Learning Dance Merak For Students lightweight disabilities in SLB C Cipaganti Bandung. Approach in this research is qualitative with research method used is Descriptive. The result of the research shows that in the learning of Merak dance in SLB C Cipagati Bandung from learning process, media and methods and learning evaluation have not run well where the dance teacher is not from dance education, the teacher does not make the learning planning, the learning is done according to his experience. And Besides, the lack of interest in learning Studentsdance Merak.